SICKLE CELL DISEASE IN HAZARA - Khan, Shaheen Pervez; Khan, Jahangir A.; Khaliq, M.A. (Journal of Ayub Medical College Abbottabad, 1990)
Sickle cell disease is group of inherited disorders of haemoglobin formation. It includes sickle cell anaemia (Hb SS), Haemoglobin SC disease (HbSC) and Sickle Cell B-Thalassaemia (HbS/BThal). Sickle Cell anaemia (HbSS) is most common and severe which is 0.3% to 1.3% in American blacks while Sickle Cell B-Thal is 0.04%.1 Sickle Cell B-Thalassaemia is double heterozygous state for Hb-S and the B-Thalassaemia is double heterozygous state for Hb-S and the B-Thalassaemia genes. It occurs mainly in persons of Greek, Italian descent and in Negroes.2 In general it resembles sickle-cell anaemia, but tends to be less severe. There are two types of sickle cell B-Thalassaemia, one is B+ thalassaemia which is characterized by incomplete suppression and B°-thalassaemia by complete absence of B-chain synthesis. It is some time difficult to distinguish between sickle-cell anaemia and S/B° thalassaemia. The pattern of the B° type closely resembles that of sickle-cell anaemia and the electrophoretic differential diagnosis usually depends on the demonstration of an increased Hb-A2 level3 in the former condition. Examination of other family members for evidence of the thalassaemia gene should be undertaken in all putative cases of sickle cell anaemia to avoid diagnostic error. The finding of an enlarged spleen in an older patient may be useful in differential diagnosis because splenomegaly is much more likely to be encountered in patients (.6 years) with S/B° thalassaemia than in homozygous sicklers. Hypochromia and microcytosis of erythrocytes is usually established by the age of one year. S/B° thalassaemia tends to be more severe than S/B+ thalassaemia. S/B° resembles more, clinically, with sickle-cell anaemia as in ocular and bony manifestations, pain, accelerated haemolysis and vasooclusion, long term anaemia, acute chest syndrome (Pneumonia or pulmonary infraction or both), and fever.4 A case report of sickle-cell B°- thalassaemia is presented here. The patient was admitted in the DHQ Hospital, Abbottabad.